Introduction to black hole physics - Frolov, V. P.; Zelnikov, Andrei (Oxford : Oxford University Press, 2011)
What is a black hole? How many of them are in our Universe? Can black holes be created in a laboratory or in particle colliders? Can objects similar to black holes be used for space and time travel? This text discusses these and many other questions providing the reader with the tools required to explore the Black Hole Land independently.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Black holes (Astronomy); Gravitational collapse; Stars -- Evolution